Fuzzy Delphi method for evaluating effective teaching based on students' perspective / Zamali Tarmudi ... [et al.] - Tarmudi, Zamali; Anas Muhiddin, Fatihah; Rossdy, Munirah; Willie D. Tamsin, Nowyannie (2016)
It has been observed that the requirement for public universities to measure effective teaching among their lecturers is an increasing concern in recent years. Since most of the criteria are usually determined by the universities, thus this paper come out with the idea that effective teaching should be assessed through students' perspectives. The study focuses on how a fuzzy approach can evaluate the identified criterion using fuzzy Delphi method (FDM). The criteria weights and effective teaching ratings are collected through a seven-point linguistic before converting into triangular fuzzy numbers (TFNs). Then, the method is equipped with three levels of confidence to offer more alternative decisions based on decision makers (DMs) final judgment. An empirical example was employed to demonstrate the applicability of the proposed method. The results show that the method has a great potential to deal with the complexity for choosing the best effective teaching among the lecturers. It offers a versatile judgment, clear in procedures and the proposed method can facilitate the universities' DMs to utilize the proposed approach for lecturers' assessment purposes.